Genomic analysis and functional properties of Lactobacillus johnsonii GJ231 isolated from healthy beagles - Zhao, Mengdi; Li, Yueyao; Zhang, Yuanyuan; Li, Guangyu (Frontiers in Microbiology, 2024)
Probiotics are one of the management tools to improve the host's healthy microbiota. The positive effects of probiotics on host health are speciesspecific, so probiotics isolated from host's own gut may be most beneficial.Many of the metabolites (e.g., short-chain fatty acids, bacteriocins, and hydrogen peroxide) produced by Lactobacillus johnsonii have specific inhibitory profiles against invading pathogens. In this study, we isolated L. johnsonii GJ231 from the intestinal tract of healthy female beagles. The genome size of 1.763 M encoded a total of 1,691 predicted genes. Many carbohydrate-active enzymes responsible for carbohydrate degradation and the production of shortchain fatty acids were also predicted. The metabolic profile of short-chain fatty acids in L. johnsonii GJ231 was determined using LC-MS/MS. The bacteriocinproducing gene bacteriocin (lactacin F) in L. johnsonii GJ231 was also predicted. In vitro, experiments demonstrated that GJ231 can thrive in weak acids, 0.3% bile salts, and artificial gastrointestinal fluid models. It was tolerant of to high temperatures up to 70°C, was non-hemolytic, inhibited pathogenic bacteria, and had a high antioxidant capacity. In vivo safety experiments conducted in mice revealed that oral administration of GJ231 not only had no toxic side effect but also increased their antioxidant capacity. In conclusion, combining the above test results, which collectively demonstrate that caninederived L. johnsonii GJ231 was a non-pathogenic, acid-tolerant and bile-salttolerant probiotic strain that inhibits pathogenic bacteria and improves host antioxidant function. This may make it a promising candidate for the development of innovative functional foods for pets.